MANAJEMEN PENDIDIKAN BERBASIS PRILAKU PADA MANAJEMEN MUTU TERPADU PENDIDIKAN DALAM PERSPEKTIF ISLAM: MANAJEMEN PENDIDIKAN BERBASIS PRILAKU PADA MANAJEMEN MUTU - Sadan Sadan (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2024)
The development of Islamic educational institutions in our country is currently experiencing rapid development, but the majority are still experiencing challenges in terms of quality. One of the problems is improved behavior management to improve quality. This study aims to explain the concept of behavior-based Islamic education management in integrated quality management of education. Through literature search, it was found that behavior management in Islamic education is based on humanitarian principles, where humans are placed as the main focus that needs attention, value, and fulfillment of their needs. The main factors that influence behavior management in Islamic educational institutions include: leadership, motivation, communication, reward and punishment systems, culture, strategic management, and integrated quality management. The role of behavior management is crucial with regard to the application of integrated quality management in Islamic education.